2014
DOI: 10.1115/1.4028528
|View full text |Cite
|
Sign up to set email alerts
|

Time-Delayed Control of SISO Systems for Improved Stability Margins

Abstract: While time delays typically lead to poor control performance, and even instability, previ-ous research shows that time delays can, in some cases, be beneficial. This paper presents a new benefit of time-delayed control (TDC) for single-input single-output (SISO) linear time invariant (LTI) systems: it can be used to improve robustness. Time delays can be used to approximate state derivative feedback (SSD), which together with state feedback (SF) can reduce sensitivity and improve stability margins. Additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 36 publications
(68 reference statements)
0
4
0
1
Order By: Relevance
“…Contrary to common belief, time delays in dynamical systems are not always detrimental to stability and performance. Several studies [19][20][21][22][23] have shown that time delays can be actively used in controllers to stabilize a system or approximate certain operations. One well-known example is the finite difference approximation in (1).…”
Section: Fully Time-based Pidmentioning
confidence: 99%
“…Contrary to common belief, time delays in dynamical systems are not always detrimental to stability and performance. Several studies [19][20][21][22][23] have shown that time delays can be actively used in controllers to stabilize a system or approximate certain operations. One well-known example is the finite difference approximation in (1).…”
Section: Fully Time-based Pidmentioning
confidence: 99%
“…The control performance of a chain of integrators is improved, when the derivative part of the controller is replaced by a delay term [36]. A number of studies address the utilization of time delays in state feedback control scheme to approximate integral and derivative terms [29,30,62]. In a recent research, Ulsoy [62] proved the positive effect of time delayed control on the disturbance rejection capability and tracking ability of a single input single output (SISO) system.…”
Section: A Review Of Favourable Effects Of Delay In Control Systemsmentioning
confidence: 99%
“…A number of studies address the utilization of time delays in state feedback control scheme to approximate integral and derivative terms [29,30,62]. In a recent research, Ulsoy [62] proved the positive effect of time delayed control on the disturbance rejection capability and tracking ability of a single input single output (SISO) system. Delay differential equation (DDE) was solved using the Lambert-W functions.…”
Section: A Review Of Favourable Effects Of Delay In Control Systemsmentioning
confidence: 99%
“…Literatürde zaman gecikmeli sistemler üzerinde yapılan bir çalışmada ise Niculescu, S. I., zaman gecikmesinin entegratör zincirleri de dahil olmak üzere lineer sistemlerin stabilizasyonu sağlamıştır (Niculescu&Michiels, 2004). Galip Ulusoy, yapmış olduğu çalışmasında, tek girişli tek çıkışlı doğrusal zamanla değişmeyen sistemler için zaman gecikmeli kontrol yapısı önermiştir (Galip, 2015). Bu kontrol yapısı kararlılık marjlarını iyileştiren ve duyarlılığı azaltmıştır.…”
Section: Introductionunclassified